2014
DOI: 10.1177/0884533614536446
|View full text |Cite
|
Sign up to set email alerts
|

Home‐Delivered Meals and Nutrition Status Among Older Adults

Abstract: The trend among older adults in the United States is to "age in place" instead of opting for institutionalization. To maintain older adults with chronic conditions in their homes and to improve health after hospitalization, comprehensive social, health, and nutrition services are essential. Quality of dietary intake is crucial and yet often underestimated. Calorie needs decrease with age while nutrient needs remain the same, even increasing for some nutrients. This poses difficulties for individuals with funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 39 publications
(42 reference statements)
0
29
0
Order By: Relevance
“…Research has also demonstrated that states that have increased their capacity in providing home-delivered meals also have recognized increased Medicaid savings by decreasing the proportion of low-care nursing home residents dually eligible for Medicaid and Medicare (Thomas & Mor, 2013). Beyond providing financial savings to states, home-delivered meals are believed to improve the quality of life of older adults: The meals improve food and nutrient intake, reduce food insecurity, and may help increase older adults’ independence while encouraging autonomy (Sahyoun & Vaudin, 2014; Zhu & An, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Research has also demonstrated that states that have increased their capacity in providing home-delivered meals also have recognized increased Medicaid savings by decreasing the proportion of low-care nursing home residents dually eligible for Medicaid and Medicare (Thomas & Mor, 2013). Beyond providing financial savings to states, home-delivered meals are believed to improve the quality of life of older adults: The meals improve food and nutrient intake, reduce food insecurity, and may help increase older adults’ independence while encouraging autonomy (Sahyoun & Vaudin, 2014; Zhu & An, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity (or food insufficiency, a measure used by researchers to estimate food insecurity without using the official questionnaire included in the CPS) in older adults has been associated with low nutrient intakes (16)(17)(18), unhealthy body weight and body size (19), poor self-related health status (17), anemia (20), multimorbidity and disability (18,21), lower cognitive function (22), anxiety and depression (19,20), and decreased quality of life (20,23). Research has shown that HDMs can improve food security status of older adults (24)(25)(26). If we are able to identify those who go into the hospital with the highest risk, we can target programs toward these individuals in an attempt to prevent food insecurity, malnutrition, and related rehospitalization and health declines.…”
Section: Introductionmentioning
confidence: 99%
“…Programs are generally popular Reprints and permissions: sagepub.com/journalsPermissions.nav with consumers and seen as beneficial in helping them to meet their basic food needs often allowing individuals to age in place (Frongillo, Isaacman, Horan, Wethington, & Pillemer, 2010;Sahyoun & Vaudin, 2014;Zhu & An, 2013). Previous research has demonstrated a relationship between state spending on home-delivered meals and the ability to keep older adults with low-care needs out of more costly care options such as nursing homes (Thomas & Mor, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Research has also demonstrated that states that have increased their capacity in providing home-delivered meals also have recognized increased Medicaid savings by decreasing the proportion of low-care nursing home residents dually eligible for Medicaid and Medicare (Thomas & Mor, 2013). Beyond providing financial savings to states, homedelivered meals are believed to improve the quality of life of older adults: The meals improve food and nutrient intake, reduce food insecurity, and may help increase older adults' independence while encouraging autonomy (Sahyoun & Vaudin, 2014;Zhu & An, 2013).…”
Section: Introductionmentioning
confidence: 99%